Leibniz and Spinozist Necessitarianism - Maunu Ari (Franz Steiner Verlag, 2022)
It is sometimes argued that Leibniz’s metaphysical commitments lead to Spinozist Necessitarianism, i.e., the view, in Spinoza’s words, that “Things could not have been produced by God in any way or in any order other than that in which they have been produced”. Leibniz comments on this passage as follows: “This proposition may be true or false, depending on how it is explained”. I suggest in this paper that what Leibniz means by this comment can be fleshed out by making a distinction between what could have been actual and what is possible. I also address some potential objections to this distinction and attempt to elaborate it by means of comparing Leibniz’s and Alvin Plantinga’s approaches to modality.